If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.7 + 0.3x = 0.6 Solving 2.7 + 0.3x = 0.6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.7' to each side of the equation. 2.7 + -2.7 + 0.3x = 0.6 + -2.7 Combine like terms: 2.7 + -2.7 = 0.0 0.0 + 0.3x = 0.6 + -2.7 0.3x = 0.6 + -2.7 Combine like terms: 0.6 + -2.7 = -2.1 0.3x = -2.1 Divide each side by '0.3'. x = -7 Simplifying x = -7
| y^2+y-45= | | 2x-5=99 | | -12a=-3-13 | | 3.6x-25=1.4x+8 | | 2x-6=9x-41 | | -5(m+2)-m-7=-6(m+5)+13 | | 0.4x+0.1=-0.3 | | x-1=5.76 | | 5x+39=14x-69 | | (5x+4)*(2x^2-9x+9)=0 | | -2p+5=-15 | | -8y=2.72 | | (5x+4)(2x^2-9x+9)=0 | | 2p^3+6p^2-5p-15= | | -8(p+1)-p-12=-9(p+4)+16 | | x*x+4=125 | | 3-3p=30 | | 2m-4=2 | | 5x+41=8x+11 | | x*x-9=30 | | 7(x-6)=5(x+2)+2x | | -3b+5=23 | | 3x+8y=0 | | 4*x*x=25 | | 3b^2-6b+yb-2y= | | 1+5x=-24 | | 3*x*x=12 | | .5y+9=.5 | | 25-10f=75 | | 3a+4=a+24 | | 100+20=3h+5h | | 2*x*x=32 |